The 2021 Lebaran Homecoming Prohibition Policy by the Government of Indonesia in A State Administrative Law Perspectivea - Zainuddin Zainuddin (RIRAI Publisher, 2021)
Officially, the government has banned the people going home on Eid al-Fitr this year. based on Circular (SE) Number 13 of 2021 concerning the End of Idul Fitri 1442 Hijriah Homecoming and Endeavors to Control the Spread of Crown Infection Illness 2019 (Covid-19) Amid the Heavenly Month of Ramadan 1442 Hijri. The Circular Letter is intended to regulate restrictions on community mobility and optimize the functions of the Covid-19 Command Post in Villages / Kelurahan during the holy months of Ramadan and Eid al-Fitr in 1442 Hijriah. The purpose of this circular letter is to prevent an increase in the spread of Covid-19 during the holy months of Ramadan and Eid al-Fitr in 1442 Hijriah. The period of eliminating Eid al-Fitr homecoming in 1442 Hijriah is May 6-17, 2021 and efforts to control Covid-19 are during the holy month of Ramadan and Idul Fitri 1442 Hijriah. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. The provisions stipulated in the Circular include protocols for eliminating homecoming, prevention and control of COVID-19; socialization; monitoring, control and evaluation; up to sanctions. Based on Circular (SE) Number 13 of 2021 concerning the Elimination of the Idul Fitri 1442 Hijriah Homecoming Day and Efforts to Control the Spread of Corona Virus Disease 2019 (Covid-19) During the Holy Month of Ramadan 1442 Hijriah that the Protocol Provisions for the Elimination of Homecoming, Prevention and Control of COVID -19.